Implementasi Akuntansi Murabahah PSAK 102 Pada Pembiayaan BSI OTO di Bank Syariah Indonesia: Meminimalisir Pembiayaan Tak Tertagih - Mulyani, Seri; Harahap, Rahmat Daim; Nurhudiani, Bella; Marhamah, Adelia; Hafnifa, Chairin; Metuah, Marpirah; Anggriani, Erni (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
Implementation of sharia accounting in accordance with accounting standards is very useful as a form of transparency and accountability of an Islamic financial institution. This study aims to analyze the application of PSAK 102 murabahah accounting to BSI OTO financing at Bank Syariah Indonesia regarding Murabahah financing. And to minimize uncollectible financing and its constraints in murabaha accounting treatment. This research uses a qualitative descriptive approach, while secondary data comes from documents relevant to this research such as annual reports, meeting minutes and financial reports from Bank Syariah Indonesia.Data analysis used in this research is descriptive analysis.